Quantum Chemical Study of Some Basic Organic Compounds as the Corrosion Inhibitors - Ahmed, Lana; Bulut, Niyazi; Kaygılı, Omer; Omer, Rebaz (Niyazi BULUT, 2023)
The corrosion inhibitor activities of 10 molecules (Benzene (C1), Phenol (C2), Toluene (C3), Benzoic acid (C4), Acetophenone (C5), Chlorobenzene (C6), Bromobenzene (C7), Benzaldehyde (C8), Naphthalene (C9), and Anthracene (C10) were investigated using quantum mechanical methods. The energy of the highest occupied molecular orbital (EHOMO), the energy of the lowest occupied molecular orbital (ELUMO), the energy bandgap (E = ELUMO - EHOMO), and the dipole moment (?) were all estimated in this study. The parameters mentioned can provide information about the corrosion efficiency of organic compounds. In addition, the density functional theory (DFT) was used to determine the geometry of the molecules as well as the electronic properties of the compounds. Physical parameters such as chemical hardness (?), softness (?), and electronegativity (?) were determined using B3LYP/6-31G (d, p). As well as the quantum chemistry properties like the fraction of electrons transported (?N) between the iron surface and the titled compounds have been calculated. This research also aimed to find which variables have a significant linear relationship with inhibitory performance. According to the results, the behavior of organic-based corrosion inhibitors is related to the effectiveness of good corrosion inhibitors and the quantum chemical parameters measured during this process. As a result, corrosion inhibitor behavior can be predicted without the need for an experiment.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik